Vocational education and training in India : challenges, status and labour market outcomes - Agrawal, Tushar [Verfasser] (My University, 2012)
"This paper provides an overview of vocational education and training (VET) system in India, and discusses various challenges and difficulties in the Indian VET system. The paper also examines labour market outcomes of vocational graduates and compares these with those of general secondary graduates using a large-scale nationally representative household survey. We find quite a high rate of unemployment (11%) for VET holders in the age group 15-29 years. Although unemployment rate of VET holders is higher than the overall unemployment rate in the same age group, the rate is lower than that for general secondary graduates. We show that average daily wages are higher, both for regular and casual workers, for VET holders. There has been a considerable increase in the number of Industrial Training Institutes/Centres in the last decades, but the coverage of the system is disparate in terms of institutes’ vis-à-vis states." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 1.3.3.1 Qualifikationsverwertung; I 2.3.4 Asien; Berufsbildungssystem; Berufsbildungspolitik; Bildungsreform; Beziehung Bildungssystem Beschäftigungssystem; Ausbildungsertrag; Indien